2015
DOI: 10.1091/mbc.e15-06-0422
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and biophysical analyses of tight junction permeability made of claudin-16 and claudin-19 dimerization

Abstract: Comprehensive biochemical, biophysical, genetic, and electron microscopic analyses of claudin-16 and -19 interactions show how claudin interaction can influence tight junction permeability and tight junction architecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 43 publications
7
53
0
Order By: Relevance
“…The finding that cldn16 and cldn19 can interact in cis but not in trans is in accordance with previous findings based on Y2H assays showing the same outcome (17,34). These studies demonstrated that cldn16 and cldn19 can form a stable dimer through the cis association of transmembrane segments 3 and 4 (34). The dependence of cldn16 TJ localization on coexpression and interaction with cldn19 is in good agreement with the finding that CLDN19 defects in humans and mice develop a phenotype similar to that of CLDN16 mutations (13)(14)(15)(16)18).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The finding that cldn16 and cldn19 can interact in cis but not in trans is in accordance with previous findings based on Y2H assays showing the same outcome (17,34). These studies demonstrated that cldn16 and cldn19 can form a stable dimer through the cis association of transmembrane segments 3 and 4 (34). The dependence of cldn16 TJ localization on coexpression and interaction with cldn19 is in good agreement with the finding that CLDN19 defects in humans and mice develop a phenotype similar to that of CLDN16 mutations (13)(14)(15)(16)18).…”
Section: Discussionsupporting
confidence: 93%
“…Its integration in TAL TJs presumably is facilitated by the heteromeric interaction with cldn19 that also interacts with cldn3 and thus allows the formation of the cldn3/16/19 TJ complex. The finding that cldn16 and cldn19 can interact in cis but not in trans is in accordance with previous findings based on Y2H assays showing the same outcome (17,34). These studies demonstrated that cldn16 and cldn19 can form a stable dimer through the cis association of transmembrane segments 3 and 4 (34).…”
Section: Discussionsupporting
confidence: 92%
“…The relationship of this to health and disease was initially shown by genetic linkage of para-cellin-1, or claudin-16, to the autosomal recessive disease of renal hypomagnesemia with hypercalciuria and nephrocalcinosis (Simon et al 1999). The divalent cation channel formed by claudin-16 (Gong et al 2015) is essential for reabsorption of magnesium and calcium ions from the urinary space. Human claudin polymorphisms have also been linked to biliary disease (Hadj-Rabia et al 2004) and deafness (Wilcox et al 2001).…”
Section: Tight Junction Molecular Architecturementioning
confidence: 99%
“…More importantly, claudin-16 and -19 physically interact (42), and loss of one claudin from the tight junction can cause the other to be endocytosed from the plasma membrane (41). In both mammalian and insect cell membranes, recombinant claudin-16 and -19 proteins form a stable cis -dimer (27). Co-expression of claudin-16 and -19 into polarized epithelial cells can confer significant cation selectivity (P Na /P Cl ) to the tight junction (27, 42).…”
Section: Thick Ascending Limb Of Henle’s Loopmentioning
confidence: 99%